Nyugdíjas Klubok és Idősek Életet az Éveknek Országos Szövetsége
National Exhibition of Folk Arts and Handicraft Artisans, 10th through 12th March 1999 organised in honour of the 10th anniversary of "Life for Years" National Association of Pensioners' Clubs and Eldery and of the International Year of the Elderly, Budapest Kálmán Bánóczky